Synergic effects of some plant-derived essential oils and Iranian isolates of entomopathogenic fungus Metarhizium anisopliae Sorokin to control Acanthoscelides obtectus (Say) (Coleoptera: Chrysomelidae) - Lak, Fatemeh; Zandi-Sohani, Nooshin; Ghodoum Parizipour, Mohammad Hamed; Ebadollahi, Asgar (Frontiers in Plant Science, 2022)
Introduction The bean weevil, Acanthoscelides obtectus, is one of the most important pests of the common bean, Phaseolus vulgaris. The pest attacks P. vulgaris seeds while they are still in the field. However, the damage continues during storage, where it causes the most significant losses. Methods The present study was conducted to evaluate the insecticidal activity, and synergic effects of three essential oils (EOs) extracted from fennel (Foeniculum vulgare), tarragon (Artemisia dracunculus), and lavender (Lavandula angustifolia), and three isolates from an entomopathogenic fungus (EPF), Metarhizium anisopliae, including IRAN2273C, IRAN2252C, and IRAN1018C against the adults of A. obtectus. The effects of EOs were also evaluated on mycelial growth and conidiation of the fungal isolates. Results and Discussion The results showed that all the EOs and the EPF exhibited insecticidal activity against A. obtectus. According to calculated LC50, L. angustifolia (1.2526 µl/l) and F. vulgare (0.9247 µl/l) EOs caused significantly higher mortality than A. dracunculus (3.1980 µl/l) against A. obtectus. The results of the pathogenicity of M. anisopliae isolates revealed that all isolates had insecticidal activity against A. obtectus. The cumulative mortality of insects varied from 59.12% in IRAN1018C to 80.86% in IRAN2273C. According to the compatibility test results, all EOs were compatible with fungal isolates except for A. dracunculus, which was toxic to the IRAN2252C isolate and showed incompatibility. The mortality of A. obtectus adults differed significantly among combined treatments of EOs and M. anisopliae isolates. According to the calculated synergic ratio, combinations of essential oils and fungal isolates had additive or synergistic effects on the mortality of A. obtectus. Based on the present findings, A. obtectus adults were susceptible to fennel, and lavender EOs, and their mortality was amplified when the EOs were combined with M. anisopliae isolates. These results can be helpful for the integrated management of A. obtectus during storage.